Malnutrition-associated factors in patients hospitalized in an emergency surgical ward in a Peruvian social security hospital - Zena-Huancas, Paola A. (2020)
Objective: to identify malnutrition-associated factors in patients hospitalized in the emergency surgical ward in Guillermo Almenara-Irigoyen National Hospital. Materials and methods: this is an analytical study in which an initial nutritional evaluation was performed using the 2002 Nutritional Risk Screening. Afterwards, a nutritional assessment was performed on admission and at discharge using a subjective overall assessment in 206 adult and elderly subjects. Clinical variables were analyzed using logistic regression and p<0.05 was considered as significant. Results: sixteen per cent of all patients worsened their nutritional status during hospitalization. Associated factors were some comorbidity (odds ratio [OR] 2.32; 95% confidence interval [CI]: 1.07-5.01); neoplasms (OR: 2.83; 95% CI: 1.21-6.63), nervous system diseases (OR: 5.66; 95% CI: 1.24-25.82); absence of weight and height recording (OR: 4.18; 95% CI: 1.29-13.41); abdominal surgery (OR: 6.67; 95% CI: 3.08-14.89); acute appendicitis decreased 85%; acute cholecystitis decreased 91%; surgical reintervention (OR: 13.91; 95% CI: 4.82-40.06); regular consumption of the indicated diet (OR: 8.78; 95% CI: 3.01-25.63); not consuming the indicated diet (OR: 39.97; 95% CI: 11.39-140.23); use of nutritional support decreased exposure by 83%. Malnutrition increased the risk of mortality 6 times. The number of days of fasting, (OR: 1.73; 95% CI: 1.31-2.27). Mortality was 8.7%. Conclusions: there are some factors associated to malnutrition during hospitalization, so it is necessary to perform screening for early detection of malnutrition when patients are admitted, and also, nutritional assessments of those found to be at risk are necessary.